TRAF1/C5, eNOS, C1q, but not STAT4 and PTPN22 gene polymorphisms are associated with genetic susceptibility to systemic lupus erythematosus in Turkey - (:unkn) unknown (ELSEVIER SCIENCE INC, 2011)
A significant source of variability in the literature on systemic lupus erythematosus (SLE) susceptibility genes has been the inability to replicate genetic findings across different racial or ethnic groups. We investigated whether a single nucleotide polymorphism (SNP) of the STAT4 (rs7574865), PTPN22 (rs2476601), TRAF1/C5 (rs10818488), and C1q (rs292001) genes as well as the 27-bp VNTR polymorphism on intron 4 of eNOS, previously associated with SLE in other populations, are also associated with SLE risk in Turkey. A group of 158 SLE patients and 155 healthy controls were included in this study. A genetic association of the TRAF1/C5, C1q, and eNOS gene polymorphism, but not of STAT4 and PTPN22, was found to confer a degree of risk for SLE. These data highlight the importance of comparative studies in different populations to confirm the previously detected genetic associations. (C) 2011 American Society for Histocompatibility and Immunogenetics. Published by Elsevier Inc. All rights reserved.
Keywords: Gene polymorphisms; Systemic lupus erythematosus; Association study; RHEUMATOID-ARTHRITIS; INCREASED RISK; VARIANTS; REGION